2018
DOI: 10.15694/mep.2018.0000100.1
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive awareness and the link with undergraduate examination performance and clinical reasoning

Abstract: Theory: Metacognitive awareness is a component of self-regulated learning and helps us to understand and control our thinking and learning. Thinking about thinking is also an important aspect of the clinical reasoning process for medical practitioners.Hypotheses: This pilot study researched the link between metacognitive awareness and undergraduate examination performance. The Metacognitive Awareness Inventory (MAI) is a validated 52 item survey instrument for measuring metacognitive awareness. It has eight su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(43 reference statements)
1
2
0
Order By: Relevance
“…This improvement in metacognition is consistent with previous studies, but generally, the literature remains inconclusive on the stage at which students typically improve their metacognition during health professional education (Siqueira et al, 2020). In previous studies with undergraduate medical students, MAI scores did not differ significantly over the span of an academic year (Hong et al, 2015) or between first-and fifth-year medical students (Welch et al, 2018). However, another study found that the MAI scores of medical students in their clinical phase were significantly higher than those of their pre-clinical counterparts (Turan et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…This improvement in metacognition is consistent with previous studies, but generally, the literature remains inconclusive on the stage at which students typically improve their metacognition during health professional education (Siqueira et al, 2020). In previous studies with undergraduate medical students, MAI scores did not differ significantly over the span of an academic year (Hong et al, 2015) or between first-and fifth-year medical students (Welch et al, 2018). However, another study found that the MAI scores of medical students in their clinical phase were significantly higher than those of their pre-clinical counterparts (Turan et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…A number of studies, including this one, demonstrate that providing no feedback, or feedback without attention to SRL processes (including self-efficacy), is unlikely to improve learning (Reynolds et al 2016), and may provide individuals with a false sense of security about their development (Brinkman et al 2015), or lead to negative learning gains (Hattie and Timperley 2007). Helping novices calibrate their confidence with their actual competence is a major challenge for medical and healthcare professions education since there is a growing body of evidence that individuals are not developing this metacognitive capability within existing training programmes (Cleary and Sandars 2011;Mavis 2001;Welch et al 2018). For prescribing and other complex technical skills such as advanced life support, appropriate calibrations are necessary when junior doctors are working in practice, often alone without supervision, and need to make safe clinical decisions (Hautz et al 2019).…”
Section: Self-efficacymentioning
confidence: 99%
“…Thus, medical students need to develop this crucial capacity and strive to strengthen it in the professional context [8]. The development of clinical reasoning skills for medical students is a key objective of medical education [9]. Clinical reasoning can be improved by motivating students to participate more actively in learning activities [10] [11] and [12].…”
Section: Introductionmentioning
confidence: 99%